Influence of surgical treatment and radiotherapy of the advanced intraoral cancers on complete blood count, body mass index, liver enzymes and leukocyte CD64 expression - Dovšak, Tadej (Radiology and oncology (Ljubljana), 2009)
Background. The aim of our study was to evaluate the influence of the surgery and radiotherapy of the advanced oral squamous cell carcinoma on the complete blood count, body mass index (BMI), acute inflam-matory response, liver enzymes and expression of the CD64 index on leukocytes in the peripheral blood. Patients and method. Venous blood was obtained from 16 patients with advanced oral squamous cell carcinomas treated with radical surgery and external beam radiotherapy. Blood samples were collected prior to surgery (T1), after surgery (T2) and after radiotherapy (T3). Blood samples were analyzed for whole blood count, immunoglobulin G levels, liver enzymes (transaminases (ALT and AST) and gammaglutamyl trasferase (?-GT)), inflammatory response markers (C-reactive protein, erythrocyte sedimentation rate, albumin, white blood count, leukocyte count and CD64 expression on leukocytes). Assessment of nutrition was done by calculating the body mass index.Results. Surgery caused anaemia, trombocytosis, leukocytosis, lymphopenia, rise in acute phase proteins, elevation of CD64 expression on monocytes and neutrophyls, elevation of liver transaminases and lowering of ?-GT, albumin, protein and bilirubin levels. After radiotherapy haemoglobin, leukocytes, C-reactive protein, erythrocyte sedimentation rate, liver transferases, albumin, bilirubin and proteins returned almost to T1 levels, levels of lymphocytes, ?-GT and body mass index lowered. IgG levels remained almost unchanged at T2 and T3. Levels of the CD64 expression on monocytes and neutrophyls also elevated after radiotherapy.Conclusions. Surgery caused a significantly larger acute phase response than radiotherapy, while radiotherapy worsened the already present lymphopenia.
Keywords: Blood Cell Count; Body Mass Index; Flow Cytometry; Jetrni, funkcijski testi; Krvnička, štetje; Liver Function Tests; Mouth Neoplasms; novotvorbe; Pretočna citometrija; Prospective Studies; Prospektivne študije; radioterapija; Radiotherapy; Receptorji, IgG; Receptors, Igg; Surgery; Telesna masa, indeks; therapy; tumor; usta; Usta, novotvorbe; zdravljenje